Современные тенденции развития инновационно-организационных структур строительной отрасли - Кулік, М. В. (Ways to Improve Construction Efficiency, 2012)
In this work the modern issues related to the management of the market place of construction and contracting services and the organization of their activities, the creation of new models of innovation and organizational structures that can function effectively in the modern construction industry.